Influence of Education on the Awareness and Perception of Civil Servants in Ogun State Secretariat towards the National Health Insurance Scheme (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: The National Health Insurance Scheme (NHIS) was established to improve healthcare access and financial protection for Nigerians. However, its effectiveness largely depends on public awareness and perception, particularly among civil servants who are key stakeholders in its implementation. Education plays a crucial role in shaping individuals' knowledge and attitudes towards health policies. This study examines the influence of education on the awareness and perception of civil servants in the Ogun State Secretariat regarding NHIS.Objectives: This study aims to assess the level of awareness and perception of NHIS among civil servants in Ogun State Secretariat, determine the effect of educational qualification on NHIS awareness, and evaluate how education influences perceptions of NHIS efficiency and accessibility. Method of Analysis: A cross-sectional survey was conducted among 350 civil servants selected through a stratified random sampling technique. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistics, including ANOVA, to examine the relationship between educational qualification and attitude towards NHIS. Results: Findings revealed that 78.3% of respondents were aware of NHIS, with 89.5% of those with tertiary education demonstrating a high level of knowledge compared to 63.2% of those with only secondary education. However, perception of NHIS effectiveness was mixed, with 52.9% expressing a poor attitude towards the scheme. Concerns about service quality, limited benefit packages, and accessibility challenges were reported by 55.7% of respondents. Furthermore, 54.3% agreed that the exclusion of epidemics and injuries from natural disasters limits NHIS effectiveness, while 45.7% believed that NHIS covers only specific drugs and diagnostic tests, restricting its full benefits. ANOVA results showed no statistically significant relationship between educational qualification and attitude towards NHIS (F = 1.450, p = 0.220), suggesting that factors beyond education influence perception. Conclusion: While education enhances awareness, it does not necessarily translate into a positive perception of NHIS. Addressing service delivery challenges, increasing policy inclusivity, and improving public trust are essential for strengthening NHIS adoption among civil servants. Future research should explore additional factors influencing NHIS participation beyond education.